2008
DOI: 10.1128/jb.00751-08
|View full text |Cite
|
Sign up to set email alerts
|

Passage through Tetrahymena tropicalis Triggers a Rapid Morphological Differentiation in Legionella pneumophila

Abstract: The intracellular bacterial pathogen Legionella pneumophila follows a developmental cycle in which replicative forms (RFs) differentiate into infectious stationary-phase forms (SPFs) in vitro and in vivo into highly infectious mature intracellular forms (MIFs). The potential relationships between SPFs and MIFs remain uncharacterized. Previously we determined that L. pneumophila survives, but does not replicate, while it transiently resides (for 1 to 2 h) in food vacuoles of the freshwater ciliate Tetrahymena t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 41 publications
4
68
0
1
Order By: Relevance
“…A hallmark virulence trait of L. pneumophila is the ability to differentiate between morphologically and phenotypically distinct states within host cells, including replicative and transmissive cell types (32,134). In some protozoan hosts, transmissive L. pneumophila differentiates further into "mature intracellular forms" suited for environmental persistence (66).…”
Section: Legionella Pneumophilamentioning
confidence: 99%
“…A hallmark virulence trait of L. pneumophila is the ability to differentiate between morphologically and phenotypically distinct states within host cells, including replicative and transmissive cell types (32,134). In some protozoan hosts, transmissive L. pneumophila differentiates further into "mature intracellular forms" suited for environmental persistence (66).…”
Section: Legionella Pneumophilamentioning
confidence: 99%
“…was grown for 5 days at 25°C. The protozoan cultures were centrifuged [T. pyriformis at 840 g for 10 min (Faulkner et al, 2008); A. castellanii and Cercomonas sp. at 540 g for 10 min (Vaerewijck et al, 2012)] and the supernatant was removed.…”
Section: Cultivation Of Flpmentioning
confidence: 99%
“…The C. jejuni packaged in expelled free MLBs was a little bigger than that in the intracellular vacuoles; the bacteria are mostly rod-shaped, and their size may exceed 2 m, with an average length of 1 m. Here, this phenomenon is probably due to the loosening of MLB membranes after expulsion into the medium, resulting from decreased pressure on the MLBs, compared with that inside the protozoal cell (54). Transmission electron micrographs of E. coli and L. pneumophila contained in MLBs also showed that the bacteria inside food vacuoles of Tetrahymena were smaller than those inside expelled MLBs (47,54).…”
Section: Discussionmentioning
confidence: 99%